Protecting Blueberries from Freezes in Florida - Jeffrey G. Williamson; Paul M. Lyrene; James W. Olmstead (EDIS)
Blueberry growers: know when the conditions are right in commercial blueberry fields, during and after bloom, for freeze damage, as well as practices you can use to minimize it. This revised 7-page fact sheet was written by J.G. Williamson, P.M. Lyrene, and J.W. Olmstead, and published by the UF Department of Horticultural Sciences, January 2012.